Influência dos antimicrobianos oxitetraciclina e imazalil sobre a decomposição da macrófita aquática Egeria najas Planch - Janke, Helena (Universidade Federal de São Carlos, 2015)
The pharmaceutical compounds residues, especially antibiotics, are among the most worrying emerging environmental contaminants. These residues potentially cause negative effects on microorganisms that play an important role in the ecosystems processes, dynamics and stability. The objective of this study was to evaluate the oxytetracycline (OTC) (against bacterium) and imazalil (IMZ) (against fungus) action on the aquatic macrophyte Egeria najas Planch decomposition in laboratory bioassays. Microcosm experiments were performed in borosilicate flasks, in triplicate, containing fragments of E. najas and water collected in Beija-Flor Reservoir, Jataí Ecological Station, Luiz Antônio, São Paulo, Brazil. The experiments were performed as follows: water and macrophyte; water with OTC and macrophyte; water with IMZ and macrophyte; water with a mixture of OTC and IMZ and the macrophyte. The OTC decay in water was also analyzed in microcosm without plant detritus addition. The experiments were kept in the dark, at 21 °C, in two experimental conditions: aerobic and anaerobic. Water pH and electrical conductivity of the systems were measured at the sampling times (1, 3, 5, 15, 35 and 65 days after the onset of the experiments). Dissolved organic carbon (DOC), total nitrogen (TN) and OTC were analyzed in the dissolved fraction. Bacterial diversity was evaluated by Denaturing Gradient Gel Electrophoresis (DGGE) and bacterial cell number counted by epifluorescence microscopy in the aqueous portion. A first-order kinetic model was adopted to describe and compare macrophyte decomposition at different treatments. The results showed that the refractory fraction decomposition and the DOC mineralization were lower in experiments containing antimicrobial OTC than in control experiments in aerobic conditions. Changes in decomposition rates were not observed in anaerobic conditions. The OTC action was not effective due to its adsorption to particulate plant material (between 61 and 65%). According to the DGGE profiles obtained for the Bacteria Domain, the bacterial community in bioassays has been modified throughout the experiment time and according to the treatment. From these results, it was concluded that antimicrobial agents can alter the rate of decomposition of detrital plant material in water, depending on environmental conditions.
Keywords: Ecologia aquática; Macrófitas aquáticas; Decomposição; Agentes antimicrobianos; Microorganismos; CIENCIAS BIOLOGICAS::ECOLOGIA